Molecular characterization of group A rotavirus strains detected in alpacas (Vicugna pacos) from Peru - Badaracco, Alejandra (2021)
The alpaca is a very important social and economic resource for the production of fibre and meat for Andean communities. Peru is the main producer of alpacas. Group A rotavirus (RVA) has been sporadically detected in alpacas. In this study, a total of 1423 faecal samples from alpacas from different locations of the Puno department in Peru were collected and analysed by an antigen-capture ELISA in order to detect RVA. Four per cent of the samples were RVA-positive (57/1423). The genotype constellation of three selected alpaca RVA strains were G3/8 P[1/14]-I2-R2/5-C2/3-M2/3-A17-N2/3-T6-E3-H3. Two of the analysed strains presented a bovine-like genotype constellation, whereas the third strain presented six segments belonging to the AU-1-like genogroup (G3, M3, C3, N3, T3 and E3), suggesting reassorting events. Monitoring of the sanitary health of juvenile alpacas is essential to reduce the rates of neonatal mortality and for the development of preventive health strategies.